Noise-Reduced and PVT-Robust Double-Balanced CMOS Mixer Using Common-Mode Feedback - Chang-Woo Lim; Ji-Young Lee; Myoung-Gyun Kim; Tae-Yeoul Yun (IEEE Access, 2023)
This paper presents a noise reduction technique using common-mode feedback in active CMOS mixers. The proposed technique decreases the common-mode noise, thus reducing the common-to-differential conversion noise arising from mismatch and process variations. In addition, the proposed technique reduces sensitivity to process, voltage, and temperature (PVT) variations due to negative feedback. A negative feedback theory is adopted to analyze the low-noise performance of the proposed technique. The theoretical analysis is validated by simulations and measurements. The conventional and proposed mixers are fabricated in a 65-nm CMOS process. Measurement results of the proposed mixer operating at an RF of 2.1 GHz show a conversion gain of 21.5 dB, the input-referred third-order intercept point (IIP3) of -16.2 dBm, and a flicker noise figure of 8.7 dB at 10 kHz while it dissipates 3.45 mW from a 1.5 V supply voltage. Measurements also show common-mode noise reduction of 10.1 dB at 10 kHz, without degradation of other characteristics. It is demonstrated that the proposed mixer can be applied to decrease phase noise of a self-oscillating mixer (SOM) due to the low common-mode flicker noise mixer.